Policy Problematics for Implementing the Merdeka Curriculum in Improving the Quality of Student Output at Madrasah Aliyah Negeri (MAN) 01 Kepahiang - Syaiful Bahri; Murni Yanto; Fitri Susanti (Indonesian Journal for Islamic Studies, 2024)
The Merdeka Curriculum is currently being widely promoted by the government through the Ministry of Education and Culture as an embodiment of new policies. The research aimed to explain the implementation of the curriculum to improve the quality of graduates, strategies for developing teaching staff as a step to improve the quality of student output and study the supporting and inhibiting factors in implementing the Merdeka curriculum. The research used qualitative methods with a descriptive approach. Data collection used observation, interviews, and triangulation analysis. To achieve learning objectives, teacher guidance is carried out through training. The research results show that the implementation of the Merdeka curriculum at MAN 1 Kepahiang is carried out through a series of management consisting of planning, regulation, implementation, monitoring and evaluation stages. In implementing the Merdeka curriculum, there are several obstacles, including insufficient availability of human resources, inadequate facilities and infrastructure, and real conditions in the field which often contradict the conditions expected by the government. Efforts to overcome these obstacles include training and competency development for teachers and education staff, increasing support from parents and the community, improving facilities and infrastructure, strengthening supervision and monitoring, and developing cooperation between stakeholders. Based on various data and information obtained, the researcher concluded that the implementation of the curriculum to improve the quality of graduates at MAN 1 Kepahiang was adjusted to the needs of the madrasah. To achieve learning goals, especially in realizing educational goals in Madrasas, it is necessary to carry out processes of planning, organizing, implementing, supervising and supervising the course of the curriculum in learning in Madrasas to advance the quality of learning, quality of education, which will ultimately support the realization of improving the quality of graduates.